Selected elements of crisis communication - Grzegorz Wojciech Pietrek; Marcel Kuhlmey (Journal of Modern Science)
Objectives The aim of this article is to identify the significance of the crisis for the functioning of the company and to find possible ways to solve it. This setting of the research objective should allow the research problem to be identified and solved as follows: how should an ‘entrepreneur’ behave in order to avoid or relatively smoothly pass through a crisis in a company.